A new species of Isoperla (Plecoptera: Perlodidae) from China - Cao, Zhishan; Wang, Ying; Li, Weihai (Zootaxa, 2020)
A new species of the perlodid genus, Isoperla Banks, I. sejila sp. nov., is described and illustrated from the Tibet Autonomous Region of southeastern China. The everted aedeagus of the male is described and the relationships with other species of this genus known from China are discussed.